SIFAT PRO-OKSIDAN SARI JERUK NIPIS (Citrus aurentifolia) TERHADAP AKTIFITAS ANTIOKSIDAN TEH HIJAU (Camellia sinensis) - sudjatini, Sudjatini (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2016)
The research was designed to understand the effect of addition of extract citrus on the antioxidative activity of green tea and to determine the optimum temperature  at the process of green tea extraction to get the best antioxidative activity.Two treatment factors were arranged in completely randomized design with three replications. First treatment factor was the temperature extraction of green tea consisted of 30, 60 and 100 oC, whereas the second treatment factor was concentration of extract citrus consisted of 0.0, 0.2, 0.4, 0.6, 0.8 and 1 %. The contents of polyphenol, tannin, total  acids were chemically determined, whereas antioxidative activity was determined by radical scavenging affect (RSA). Data were analyzed using analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) if there was a significant difference in treatment effects.The research’s results show that there was insignificant interaction between temperature extraction of green tea and concentration of added extract citrus. Eventhough concentration of extract citrus did not significantly affect the contents of polyphenol and tannin but it affected significantly the contents of total acids and antioxidative activity of extract tea. The antioxidative activity at the concentration of extract citrus of 0.2 % was significantly greater than without extract citrus (as check treatment). The following increase in concentration of extract citrus until 1 % did not significantly increase in antioxidative activity. The temperature of tea extraction affected significantly on the contents of  polyphenol, tannin, total acids, and antioxidative activity of extract green tea. The highest values were obtained  at 100 oC and the the lowest at 30 oC. Temperature extraction of green tea of 100 oC and the addition of 0.2 % extract citrus was the optimum condition. At this condition,  the extract green tea contained polyphenol, tannin, total acids, and antioxidative activity as high as  13.77, 12.77, 0.69 and 93.37 %, respectively.